Aproveitamento de Recursos Hídricos em Micro Bacias Hidrográficas Utilizando Sistemas de Informação Geográfica - RENUNCIO, LUIZ ERNESTO; LOCH, CARLOS (Pesquisas em Geociências, 1997)
The daily increase of inhabitants in our cities, when associated with the commercial and industrial development, leads to larger water consumption demand. Despite the larger demand the resource may maintain its quality. The solutions to these difficult problem frequently require the capacity to store manage and analyze large databases, spatially distributed. This work presents the methodology adopted to plan and locate the best site for a water supply reservoir, with the aggregation of a GIS structured database, regarding a microbasin as the planning unit. This was held in the municipality of Cocal do Sul, Brazil. The result was a previous location for the water supply reservoir, considering also other uses for the water that should be stored.